2013
DOI: 10.1111/jofo.12041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated investigator handling of Leach's Storm-Petrel chicks on growth rates and the acute stress response

Abstract: Disturbance during development may have lasting effects on the growth rates and stress physiology of birds. Although repeated handling by researchers is often necessary, the possible effects of such handling on the development of semi‐altricial young are unclear. We examined the effect of daily handling on growth rates and plasma corticosterone levels of Leach's Storm‐Petrel (Oceanodroma leucorhoa) chicks on Kent Island in the Bay of Fundy, New Brunswick, Canada, during the 2011 nesting season. From post‐hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Something to be cognizant of in survival and other CMR studies is investigator disturbance, which can influence reproductive success and potentially lead to nest abandonment (Blackmer et al 2004, Carey 2009but see O'Dwyer et al 2006, Fiske et al 2013. Burrows on Bon Portage Island were visited only twice during incubation, which should be associated with infrequent abandonment (Blackmer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Something to be cognizant of in survival and other CMR studies is investigator disturbance, which can influence reproductive success and potentially lead to nest abandonment (Blackmer et al 2004, Carey 2009but see O'Dwyer et al 2006, Fiske et al 2013. Burrows on Bon Portage Island were visited only twice during incubation, which should be associated with infrequent abandonment (Blackmer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…, Fiske et al . ). It is probably maladaptive for cavity‐dwelling chicks, such as those of Storm Petrels, which are unable to escape or defend themselves in the event of a predation attempt, to elicit an adrenocortical response to an acute stressor.…”
Section: Discussionmentioning
confidence: 97%
“…Despite being capable of eliciting an adrenocortical response to a standardized stressor (albeit somewhat reduced compared to adults), Fiske et al . () demonstrated that daily handling had no effect on either baseline or stress‐induced CORT levels or growth rate in nestlings of the Leach's Storm Petrel. Not only was handling at a high intensity (daily) in this study, but it was also confined to the first half of postnatal development (maximum of 29 days post‐hatch).…”
Section: Discussionmentioning
confidence: 98%
“…While it is not certain if nestling storm petrels can elicit an acute adrenocortical response to a stressor, the young of related species have been shown to exhibit a robust acute stress response shortly after hatching, albeit greatly reduced compared with adults ( Adams et al , 2008 ; Fiske et al , 2013 ; Quillfeldt et al , 2009 ). Such hyposuppression of the HPA axis has been demonstrated in many vertebrates and is assumed to be adaptive, by preventing exposure to excess GCs during the vulnerable period of development ( Wada et al , 2007 ).…”
Section: Discussionmentioning
confidence: 99%